2013
DOI: 10.1177/0272989x12465490
|View full text |Cite
|
Sign up to set email alerts
|

How to Discriminate between Computer-Aided and Computer-Hindered Decisions

Abstract: Background. Computer aids can affect decisions in complex ways, potentially even making them worse; common assessment methods may miss these effects. We developed a method for estimating the quality of decisions, as well as how computer aids affect it, and applied it to computer-aided detection (CAD) of cancer, reanalyzing data from a published study where 50 professionals (“readers”) interpreted 180 mammograms, both with and without computer support. Method. We used stepwise regression to estimate how CAD aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 30 publications
(105 reference statements)
2
49
0
Order By: Relevance
“…Despite the great potential for ML to assist in medical diagnoses, previous research has reported a risk of a deterioration in diagnostic accuracy on some occasions. For example, in a study of 50 expert clinicians, there was up to a 14% decrease in diagnostic sensitivity when presented with challenging images marked by computer-aided detection 36 . Another study of 30 internal medicine residents showed that the residents exhibited a decrease in diagnostic accuracy (from 57% to 48%) when electrocardiograms were annotated with inaccurate computer-aided diagnoses 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great potential for ML to assist in medical diagnoses, previous research has reported a risk of a deterioration in diagnostic accuracy on some occasions. For example, in a study of 50 expert clinicians, there was up to a 14% decrease in diagnostic sensitivity when presented with challenging images marked by computer-aided detection 36 . Another study of 30 internal medicine residents showed that the residents exhibited a decrease in diagnostic accuracy (from 57% to 48%) when electrocardiograms were annotated with inaccurate computer-aided diagnoses 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Finding evidence of omission errors in the computer-aided detection of cancers in screening mammography [15, 16] and commission errors in the computerized interpretation of EKGs, [17] answering clinical questions assisted by CDS, [18] and deciding what to prescribe for clinical scenarios [19]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been a small number of studies conducted in healthcare, finding evidence of AB omission errors in computer-aided detection of cancers in mammograms, [15, 16] and commission errors in the computerized interpretation of EKGs, [17] and answering questions about clinical scenarios [18]. Goddard, et al [19] found evidence of commission errors, where general practitioners answered questions about which drugs they would prescribe for different clinical scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, users may believe a system to be more reliable than it actually is and misuse it by agreeing with incorrect suggestions, a behavior known as over-reliance [3]. Previous studies have shown that over-reliance is widespread in CDSS use [2,4,14,25,26] and that it can be more pronounced in users with low confidence in their abilities or judgment [18]. This is a major concern when targeting a CDSS at clinicians who do not have specialized knowledge.…”
Section: A System Reliability and Usementioning
confidence: 99%